Increasing Human Papillomavirus Vaccine Coverage Among Men Who Have Sex With Men—National HIV Behavioral Surveillance, United States, 2014. (1st July 2017) - Oliver, Sara E.; Hoots, Brooke E.; Paz-Bailey, Gabriela; Markowitz, Lauri E.; Meites, Elissa
Abstract : Background: Human papillomavirus (HPV) can cause oropharyngeal and anogenital cancers among men who have sex with men (MSM). In 2011, the Advisory Committee on Immunization Practices (ACIP) extended HPV vaccine recommendations to males through age 21 and MSM through age 26. Because of this distinction, vaccination for some MSM might rely on sexual behavior disclosure to health care providers. Receipt of ≥1 HPV vaccination among MSM aged 18–26 in National HIV Behavioral Surveillance (NHBS) was 4.9% in 2011. We evaluated HPV vaccine coverage and associated factors among MSM in 2014. Setting: Twenty US metropolitan statistical areas in 2014. Methods: Coverage was calculated as percentage of MSM self-reporting ≥1 HPV vaccination. Adjusted prevalence ratios were calculated from Poisson regression models to estimate associations of demographic and behavioral characteristics with HPV vaccination. Results: Among 2892 MSM aged 18–26 years, HPV vaccine coverage was 17.2%. Overall, 2326 (80.4%) reported a health care visit within 12 months, and 2095 (72.4%) disclosed MSM attraction or behavior to a health care provider. Factors associated with vaccination included self-reported HIV infection; having a health care visit within 12 months, health insurance, or a usual place of care; and disclosing MSM attraction or behavior to a health care provider. Conclusions: Since the 2011 recommendation for vaccination of males, HPV vaccine coverage among MSM increased, but remains low. Most MSM reported a recent health care visit and disclosed sexual behavior, indicating opportunities for vaccination. Potential strategies for increasing MSM coverage include improving access to recommended care, and offering education for providers and patients. Abstract : Supplemental Digital Content is Available in the Text.